Supply Chain and Open Innovation: the undeniable relationship Conceptions from a literature review - Dorrego, Juan Ignacio; Lazzarotti, Valentina; Collazzo, Pablo (Empresa y Sociedad, 2024)
The consolidation of Open Innovation (OI) as necessary approach to understand the ability of firms to innovate has demanded more sustained efforts to unfold the continuous connection with other relevant actors across its systems of production (Arabshahi et al., 2014; Chesbrough, 2006; JimenezJimenez et al., 2019). Central to this is the emphasis on a pursuit of knowledge and collaboration from components of the supply chain (SC) (Miyamoto, 2020). Despite the undeniable relationship between these two terms, authors have pointed out that not enough research has occurred (Ardito et al., 2020; Jimenez-Jimenez et al., 2019; R. A. E. Shamah & Elssawabi, 2015; Smith & Blundel, 2012). Therefore, this paper is intended to contribute to the research gap by examining on how the concepts of SC and OI are related in the current state-of-the-art. To accomplish it, a systematic literature review (SLR) is conducted.